"Esse é o legítimo tá pessoal": o discurso dos vendedores informais em situação de trabalho - Requena, Maisa Aparecida (2009)
The study of diversities of creative manifestations in Brazilian people has allowed us to find out personages who discovered an alternative of work to face the unemployment: to produce publicity and selling products inside the Metropolitan trains of São Paulo. It is about the discourses produced by the informal worker whose advertising does not appear in magazines, newspaper, pamphlets, outdoors etc., but have the same goals, which are to publicize, spread ideas and, mainly, to sell products. In this sense, this research has as its objective to analyze the discursive mechanism that characterize the speeches of these informal workers. The research conforms to the theoretical field developed by Dominique Maingueneau, more specifically in the conceptions of Interdiscourse, Scenography and Ethos. From the methodological point of view, we have followed these steps: (i) the observation of the work activities of the workers the discourses produced by them, (ii) field notes about the activity in work circumstances and about the discourses transmitted by the workers and (iii) transcription of some of their speech. The analysis has revealed two groups of discourse: the slogan-discourses and the advertisement-discourse. The first one has showed an enunciative scene compatible with the street market conditions, while in the second one, the developed scene was similar to the auction situation. From the scenography analysis, it has emerged the Ethos of the enunciators of both groups. In the slogan-discourse, the presented Ethos is from an agile, discreet and invisible enunciator, while in the advertisement-discourse, the presented Ethos is from a good-tempered, calm, sympathetic, agile and considerate enunciator. Thus, the workers mobilize many mechanisms in order to create a new model of publicity that aims to legitimate its discourses, generating scenographies and presenting an Ethos